In vitro bioaccessibility for health risk assessment of metal contamination in urban dust and soil samples: A chemometric approach / Ibrahim Sani Shabanda - Ibrahim Sani , Shabanda (2019)
Anthropogenic activities in urban cities may pose a risk to human health and environment. For risk assessment studies, estimation of contaminants in environmental media is always depending on the concentration of metals determined in the matrices. Nevertheless, the metal fractions that are taken up by the human body via exposure routes are of topmost concern. The focus of this work is to assess these fractions of contaminants, through the application of a bioaccessibility protocol for health risk estimation via oral exposure. Therefore, arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), and lead (Pb) were determined in soil and urban dust samples using Inductively Coupled Plasma Mass Spectrometry technique (ICP-MS). The sampling location chosen in this study was Petaling Jaya and Sekinchan involving ninety-four urban dust and twenty-one soil samples. Total concentration of As, Cd, Cr, Cu, Ni and Pb were determined in urban dust using multivariate analysis. The result obtained shows that the concentrations of these metals in both urban dust and soils were found to be higher than their corresponding background values, indicating anthropogenic influence in the contamination of the metals. The enrichment factor (EF) analysis shows that all the metals have EF values greater than 1.5, suggesting anthropogenic influence. The multivariate analysis conducted revealed that anthropogenic activities, atmospheric deposition and wind could be the sources of the heavy metals (HMs) in the study area. The potential ecological risk assessment indicates that Cd was the main ecological risk factor in urban dust with the order Cd > Pb > Cu > As > Ni > Cr. The oral bioaccessibility of the heavy metal contaminants were determined in both dust and soil samples using a developed Physiologically Based Extraction Test (PBET). The results obtained revealed that the contaminants were more solubilized in the gastric phase than of the intestinal phase for all the samples. Based on the results, more than 40% of the total concentration of the metals were solubilized in the gastrointestinal tract of soil, while the percentage increases up to 80% for urban dust. The result of the health risk assessment of the HMs via oral ingestion of dust and soil following Monte Carlo simulation (MC) analysis shows that for both children and adults who ingest urban dust and soil pose no significant possibility of non-carcinogenic effects, while adults could have carcinogenic consequences on ingestion of Cd in soil. Nevertheless, children are more vulnerable to non-carcinogenic risks, whereas, adults were more susceptible to cancer effects. Moreover, the risks estimation following ingestion of dust without bioaccessibility was higher than the risks accounting with bioaccessibility. This implies the importance of bioaccessibility in health risk assessment. The risks assessed without bioaccessibility seems to be overestimated. Therefore, bioaccessibility is an absolutely essential ingredient for accurate health risk evaluations of HMs exposure via oral ingestion of dust and soil.